БЕЗОПАСНОСТЬ ИНГИБИТОРОВ АНГИОТЕНЗИНПРЕВРАЩАЮЩЕГО ФЕРМЕНТА В РАННИЕ СРОКИ БЕРЕМЕННОСТИ - Ф. И. Белялов (SINAPS LLC, 2015)
We systematically reviewed the studies evaluating the risk of major malformations. Studies results suggest that first trimester exposure to angiotensin converting enzyme inhibitors is not associated with an elevated risk of major malformations compared with other antihypertensives.